A Preliminary Account of the Northern Toussian Balafon Surrogate Language - Struthers-Young, Anthony (Frontiers in Communication, 2022)
Northern Toussian is a language spoken in southwest Burkina Faso. Like many of the ethnicities in the region, members of the musical caste, the griots, have developed a musical surrogate language which is played on the balafon. This article is a preliminary documentation of the Northern Toussian balafon surrogate language, describing its cultural usage, analyzing how the tones of the spoken language are encoded in the surrogate language, and comparing the Northern Toussian surrogate language with the neighboring Sambla surrogate language. It was found that the Northern Toussian surrogate language encodes significantly more post-lexical features of the spoken language than the Sambla surrogate language, such as downdrift.